Hypervelocity impact tests on a Whipple shield using a flyer plate in the velocity range from 4 km/s to 12 km/s. (October 2021) - Song, Zhenfei; Pei, Xiaoyang; Yu, Jidong; Zhao, Jianheng; Tan, Fuli
Highlights: We get Hypervelocity impact test data for a Whipple shield consistently using a polymer plate in the velocity range from 3 km/s to 12 km/s. The development of the obtained ballistic limiting curve (BLC) versus impact velocity depends on the solid-to-liquid phase transformation based on the aluminum high-pressure phase diagram. The obtained BLC has three minima, exactly corresponding to the occurrence of melting under interactions among multiply rebounded stress pulses, under the first releasing wave which propagates through shock-compressed bumper sheet, and under the direct shock compression, respectively. The shock-induced direct melting beginning at about 120 GPa for aluminum will lead to the formation of a debris cloud which consists of widely-spread fine fragments. The BLC tested by the flyer plate goes upward abruptly. It provides useful knowledge for predicting the BLC by a sphere at impact velocities exceeding 7 km/s. Abstract: A Mylar flyer plate, being launched by an electric gun, has been applied to explore the ballistic performance of a 2024 alloy Whipple shield consisting of a 1.0-mm-thick bumper and a 3.2-mm-thick rear wall with a standoff of 70 mm between them. In comparison with a spherical projectile, experimental results show that the polymer plate, having about one-fourth mass of an aluminum sphere, can penetrate the same Whipple at impact velocities of 3 km/s and 5 km/s. The ballistic limit curves (BLCs) of the Whipple are obtained in the velocity range from 3 km/s to 12 km/s using 0.25-mm-thick and 0.5-mm-thick Mylar flyers at normal and/or oblique impacts. Different from spherical projectile, the BLCs obtained by a flyer plate oscillate abruptly with impact velocity. The development of the BLC depends on both the spreading feature of the fragmented bumper sheet and the kinetic energy it carries. In normal impact condition, the BLC turns to go upward at the flyer/bumper shock pressures of 41 GPa, 71 GPa and 121 GPa, exactly corresponding to the occurrence of melting in bumper materials under the interactions among rebounded stress pulses, under the first releasing wave propagating through shock-compressed state, and under direct shock compression, respectively. Among the three melting mechanisms, the shock-induced melting produces the most widely spread debris cloud with the finest fragments.